The Thymic Orchestration Involving Aire, miRNAs, and Cell–Cell Interactions during the Induction of Central Tolerance - Passos, Geraldo Aleixo; Mendes-da-Cruz, Daniella Arêas; Oliveira, Ernna Hérida (Frontiers in Immunology, 2015)
Developing thymocytes interact sequentially with two distinct structures within the thymus: the cortex and medulla. Surviving single-positive and double-positive thymocytes from the cortex migrate into the medulla, where they interact with medullary thymic epithelial cells (mTECs). These cells ectopically express a vast set of peripheral tissue antigens (PTAs), a property termed promiscuous gene expression that is associated with the presentation of PTAs by mTECs to thymocytes. Thymocyte clones that have a high affinity for PTAs are eliminated by apoptosis in a process termed negative selection, which is essential for tolerance induction. The Aire gene is an important factor that controls the expression of a large set of PTAs. In addition to PTAs, Aire also controls the expression of miRNAs in mTECs. These miRNAs are important in the organization of the thymic architecture and act as posttranscriptional controllers of PTAs. Herein, we discuss recent discoveries and highlight open questions regarding the migration and interaction of developing thymocytes with thymic stroma, the ectopic expression of PTAs by mTECs, the association between Aire and miRNAs and its effects on central tolerance.